Inhaled Nanoformulated mRNA Polyplexes for Protein Production in Lung Epithelium. Issue 8 (4th January 2019) - Patel, Asha Kumari; Kaczmarek, James C.; Bose, Suman; Kauffman, Kevin J.; Mir, Faryal; Heartlein, Michael W.; DeRosa, Frank; Langer, Robert; Anderson, Daniel G.
Abstract: Noninvasive aerosol inhalation is an established method of drug delivery to the lung, and remains a desirable route for nucleic‐acid‐based therapeutics. In vitro transcribed (IVT) mRNA has broad therapeutic applicability as it permits temporal and dose‐dependent control of encoded protein expression. Inhaled delivery of IVT‐mRNA has not yet been demonstrated and requires development of safe and effective materials. To meet this need, hyperbranched poly(beta amino esters) (hPBAEs) are synthesized to enable nanoformulation of stable and concentrated polyplexes suitable for inhalation. This strategy achieves uniform distribution of luciferase mRNA throughout all five lobes of the lung and produces 101.2 ng g −1 of luciferase protein 24 h after inhalation of hPBAE polyplexes. Importantly, delivery is localized to the lung, and no luminescence is observed in other tissues. Furthermore, using an Ai14 reporter mouse model it is identified that 24.6% of the total lung epithelial cell population is transfected after a single dose. Repeat dosing of inhaled hPBAE‐mRNA generates consistent protein production in the lung, without local or systemic toxicity. The results indicate that nebulized delivery of IVT‐mRNA facilitated by hPBAE vectors may provide a clinically relevant delivery system to lung epithelium. Abstract : In vitro transcribed mRNA is nebulized using poly(beta amino esters) for noninvasive delivery to the lung. Hyperbranched polymers form stable mRNA‐polyplexes that distribute uniformly throughout the lungs of mice after inhalation. Reporter protein is expressed in 24.6% of the total lung epithelial cell population after a single dose and repeat dosing results in consistent protein levels without toxicity.